Management and organisational behaviour - Mullins, Laurie J. (Financial Times Prentice Hall, 2010)
Presenting a managerial approach to the study of organisational behaviour, with an emphasis on improving working performance through a better understanding of human resources, this book contains summaries, review questions and assignments.